Peningkatan Literasi Awal Anak Usia Dini melalui Program Pojok Baca KKN Fakultas Ekonomi Universitas Krisnadwipayana di Desa Tugu Utara, Cisarua, Bogor - Amilia Hasbullah; Ahmad Hermanto; Dhistianti Meirahmawantari; Rachmaniar. M. Dwiputri; Siwi Nur Indriyani; Wiwik Rachmarwi; Freddrick Tiagita Putra (Lembaga Pengembangan Kinerja Dosen, 2024)
Developing an interest in early childhood reading is the initial step towards recognizing the significance of literacy in society. Early childhood literacy is an essential part of the language development process and has a significant role in enhancing the overall quality of education. The presence of appropriate facilities and resources in a school setting plays a crucial role in promoting reading engagement among children who are in their early years of education. The reading interest program not only goes government accountability, but it also allows the public to contribute to the sustaining of such efforts. As part of its community service efforts, the Faculty of Economics at the University of Krisnadwipayana places special emphasis on early childhood education. This project entails educators and students collaborating to create and implement a reading corner program in Desa Tugu Utara, Bogor. This program has a significant influence on the implementation of early literacy activities for kids of all ages, which are set up by the community service team of the Faculty of Economics at the University of Krisnadwipayana.